Infrared Spectroscopy of Ethanethiol Monomers and Dimers at MP2 Level Characterizing the Dimer Formation and Hydrogen Bond - Brito, Airan F S (Journal of computational chemistry, 2025)
© 2024 Wiley Periodicals LLC.